The role of mentoring activities in teacher training – lessons from a pilot study conducted amongconductor-teacher specialist students (Training and Practice : Journal of Educational Sciences, 2024)
The role of a mentor in the life of a school is clearly significant. Since the initial experience of a new teacher is a crucial factor in determining whether or not he or she remains in the profession, the quality of the mentoring is not irrelevant. In teacher education, the training school is the place where students put into practice the theories they have learned in higher education. Both the institution and the teachers who mentor them are of great importance, since it is here that a teacher trainee first encounters the teaching profession ’live’. Using the literature already published on this topic and further reflecting on it, I explored the attitudes of the students of the Pető András Faculty of Conductor-Teacher Specialisation at Semmelweis University towards external practice, their opinions on mentoring, the impact of the mentor-student relationship on the success of the practice, and the factors influencing the career socialisation of the students. I identified their needs and the help and support they expected from their mentor.
Keywords: mentor; early career teacher; career socialisation